SYSTEM DYNAMICS MODEL OF THE MORTGAGE LENDING MARKET IN RUSSIA - Anna V. Nikolaeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article describes one of the currently existing schemes of mortgage crediting in Russia. Key components of the banking system in view of mortgage crediting were presented, their basic characteristics were displayed. On the basis of this scheme the article builds a system and dynamic model of the bank, which allows us to trace the dynamics of the mortgage market in recent years. Adverse consequences of economic sanctions and volatile nature of the national currency were analyzed. Principle risks typical of mortgage crediting within the period of economic crisis were evaluated. The author puts forward a scenario analysis of prospects of market development in the near future.